Performance control considering risks for construction projects - Cuadros López, Alvaro Julio; Rangel Collazos, Vanessa; Aguilar, Cristina (Scientia et Technica, 2019)
Making decisions during the building phase of a project is much important for their success. To support that process, it has developed the Earned Value Management system which considers scope, time and cost to measure the project performance and to identify variances from the original plan. By identifying performance variances, the Project Manager has to do corrective actions for correcting the course of the project. The EVM is a deterministic method so any variance reported is considered a performance problem that needs to be attended. This characteristic is currently considered a weakness of the method for being applied in daily operations. The paper presents an EVM-based method for controlling time and cost that allows the project manager to determine when really needed corrective actions are. The proposal was applied in a construction project to evaluate its utility.